Continuing to Increase Investigation in Uzbekistan and Actively Attract Foreign Investment as a Factor of Sustainable Economic Growth - Gaibullaev Rakhim Murodovich (Research Parks Publishers, 2022)
The article outlines the approaches to investment policy in the country, the system of investment attractiveness and financial support for entrepreneurship and increasing investment activity, attracting foreign investment as one of the sources of funding.